Analysis of Soil Insect Diversity as Bioindicator of Post-Mining Land Reclamation Success Rate: Case Study at West Banko Area, PT Bukit Asam - Kamal, Mustafa; Ramadhani, Audya Rahma; Oktariansyah, Yadi (BIOVALENTIA: Biological Research Journal, 2025)
Open-pit coal mining damages habitat, alters soil, and lowers biodiversity, therefore harming the ecosystem. Efforts at land reclamation involving topsoil restoration and regrowth are very vital for ecological recovery. This study uses soil insect diversity as a bioindicator of West Banko area PT Bukit Asam, South Sumatera, reclamation success. Soil insects were collected using combinations of soil extraction and forest floor collection methods along transect lines. Environmental factors like soil temperature, pH, humidity, and light intensity were measured to determine habitat conditions. Data demonstrates that Formicidae (Camponotus spp.) dominates the total of 154 soil insect individuals across eight genera, four families, and three orders. Considering excellent development in the restoration effort, the Shannon-Wiener diversity index (H') = 1.80656 indicates a minor degree of biodiversity. But the preponderance of monoculture Eucalyptus plants may limit insect diversity. increased soil humidity levels (60–80%) linked with increased insect population, therefore underlining the significance of soil moisture in the regeneration of ecosystems. The findings underline the need for different vegetation in reclamation strategies to help in better ecological balance and biodiversity. This study would be rather helpful for policymakers to focus on land restoration projects for ecologically acceptable post-mining ecosystem regeneration.